Study Of The Effect Of Driver Load On Power Consumption Of 500 Watt Capacity Electric Bicycle - Yasin, Fahmi Ali; Widhining, Diah Arie; Rizal, Royb Fatkhur (ENERGY: JURNAL ILMIAH ILMU-ILMU TEKNIK, 2023)
Electric - based transportation modes are increasingly increasing in use due to the development of electric motor technology, control devices, and batteries. The problem that arises is that the power consumption of different driver loads is unknown. This research is a study of power consumption proven on an electric bicycle type GODA 140. Electric bicycles are tested with the same mileage and some differences in changes in rider load, road construction and speed difference. The results obtained in mode 1 with the rider load doubled (59 k g - 118 kg) showed that the maximum speed decreased by 10% while the power consumption increased from 274.9 watts to 520.2 watts. The battery voltage decreased when the 59 k g load decreased by 1 V, when the 118 k g load decreased by 2.58 V. In mode 2 with the rider load doubled (59 kg - 118 kg), the maximum speed decreased by 10%, while the power consumption increased from 373.2 watts to 564.7 watts. The battery voltage decreased when the load of 59 kg decreased by 1 V, when the load of 118 kg decreased by 3.06 V. In mode 3 with the rider load doubled (59 kg - 118 kg), the maximum speed decreased by 11.1%, while the power consumption increased from 394.6 watts to 628.2 watts. The battery voltage decreased when the 59 kg load decreased by 1 V while the 118 kg load decreased by 3.1 V